Detection of Parasites Contaminating Raw Consumable Vegetables in Kalar City, Kurdistan Region, Iraq - Hazhar M. Aziz (ASJ - Academic Science Journal, 2023)
Intestinal parasitic infections are one of the most important health problems. Although freshvegetables are considered as a vital element of a healthy diet, they are a potential source ofhuman intestinal parasitic infections during production, collection, transportation, preparationand consumption. The present study was carried out to determine and detect the parasitecontaminants of fresh vegetables that are sold at different open-aired markets in Kalar city,Kurdistan Region, Iraq. A total of 240 raw vegetable samples were examined by sedimentationtechnique after washing the samples with normal saline. Of the 240 samples, 124 (51.7%) weremicroscopically positive for intestinal parasites. Particularly, a high rate of contamination wasrecorded in cress (Lepidium sativum) with 70%. However, the least contaminated sample waslettuce (Lactuca sativa) with 36.7%. The most encountered parasite was Taenia spp. (egg12.9%), whereas Trichuris trichiura (0.83%) was the least detected parasite. Since, the resultsemphasize the fresh vegetables are potential sources of transmission for intestinal parasites incentral markets of Kalar city, strict hygienic measures should always be adopted to avoidparasitic contamination. Untreated sewage and the manure used by greengrocer as fertilizer canbe implicated in vegetable contamination.